2013
DOI: 10.1002/job.1902
|View full text |Cite
|
Sign up to set email alerts
|

Developing a passion for work passion: Future directions on an emerging construct

Abstract: Summary Although the passion that people demonstrate at work would appear to be a topic of considerable interest and importance to organizational scholars and practitioners, we know virtually nothing about it. In response, we introduce the work passion construct, discuss what we currently understand, and provide needed directions for future research. Copyright © 2013 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
133
0
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(148 citation statements)
references
References 18 publications
(31 reference statements)
2
133
0
13
Order By: Relevance
“…Practitioners and researchers alike have been calling for passion for work as means for wellbeing and performance (Allegretti, 2000;Boyatzis, McKee, & Goleman, 2002;Cardon, Wincent, Singh, & Drnovsek, 2009;Locke & Latham, 2004;Martin, 2004;Perrewé, Hochwarter, Ferris, McAllister, & Harris, 2013;Zigarmi, Nimon, Houson, Witt, & Dichl, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Practitioners and researchers alike have been calling for passion for work as means for wellbeing and performance (Allegretti, 2000;Boyatzis, McKee, & Goleman, 2002;Cardon, Wincent, Singh, & Drnovsek, 2009;Locke & Latham, 2004;Martin, 2004;Perrewé, Hochwarter, Ferris, McAllister, & Harris, 2013;Zigarmi, Nimon, Houson, Witt, & Dichl, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have addressed the need to investigate how this dualistic model fits in the organizational landscape (Ho, Wong, & Lee, 2011;Liu et al, 2011;Perrewé et al, 2013). The dualistic model of passion was introduced to fill a void in the extant literature on passion for activities (Vallerand et al, 2003); yet, to our knowledge, no study have rigorously investigated whether this void also exists in the work attitude literature and whether passion for work fills this void.…”
Section: Introductionmentioning
confidence: 99%
“…However, the scholarly sport management community knows little about the concept of passion, since studies in this area have been empirically limited to football fans (Vallerand et al, 2008a), referees (Philippe et al, 2009), and professional athletes (Donahue et al, 2009;Vallerand et al, 2006), thereby neglecting the sport organisations' administrative personnel; that is, the potential backbone of the constant growth seen in the sport ecosystem across the globe. This is rather surprising considering that -albeit outside the sporting contextscholars and practitioners have emphasised not only the personal benefits of being passionate about one's job (Boyatzis et al, 2002;Perrewé et al, 2014), but also the organisational gains that can be derived from organisations having passionate employees (Bruch and Ghoshal, 2003;Ho et al, 2011). Moreover, Todd and Kent (2009) suggested that the attractiveness of the sport industry workplace rests on the assumption that sport employees "derive certain emotionally significant benefits from their 'group membership' in sport organisations in excess of what may be seen in other industries" (p. 174).…”
Section: Consequently Various Institutions (Such As Governments Promentioning
confidence: 99%
“…Existe una necesidad de diferenciar los constructos organizacionales relacionados a la pasión para que se facilite la investigación sistemática, el desarrollo de intervenciones adecuadas y para preservar la parsimonia por la que se debe regir toda teoría científica (Le, Schmidt, Harter & Lauver, 2010;Perrewé et al, 2014;Salanova & Schaufeli, 2009). La psicología positiva se ha encontrado con algunas críticas hacia la falta de rigurosidad metodológica, ideológica y conceptual de la investigación (Hackman, 2009).…”
Section: Conceptos Similaresunclassified
“…A pesar de la gran cantidad de investigaciones que se ha generado sobre la pasión por el trabajo, existe confusión con otros conceptos similares propios de la psicología ocupacional (Perrewé, Hochwarter, Ferris, Mcallister & Harris, 2014). Un ejemplo claro de esta polémica es el libro publicado por algunos de los exponentes principales del engagement en el trabajo, Salanova y Schaufeli (2009), El engagement en el trabajo: cuando el trabajo se convierte en pasión.…”
Section: Introductionunclassified